A squaraine-based colorimetric and F− dependent chemosensor for recyclable CO2 gas detection: highly sensitive off–on–off response1. Issue 72 (18th September 2015) - Xia, Guomin; Liu, Yang; Ye, Benfei; Sun, Jianqi; Wang, Hongming
<x xml:space="preserve">Abstract</x> An unsymmetrical squaraine-based chemosensor SH2 has been synthesized, and its sensing behavior towards CO2 gas was described in detail by UV-vis and 1H NMR spectroscopies in DMSO.